Analysis of Professor Wu Kun’s Philosophy of Information - Duan, Yong (Transactions on Economics, Business and Management Research, 2024)
Professor Wu Kun established a profound Information Philosophy system in 2004, this is a great theoretical exploration, which has profound theoretical value. But I have a great difference with Professor Wu. Professor Wu distinguished three essences of the concept of information: signal, source and consciousness. Professor Wu’s mistake is to confuse associations with signals, and he thought that signals themselves are not real. The reason why the "catching moon in the water" is absurd is not because the moon in the water is unreal, but because the association that people have after seeing the moon in the water is unreal. I believe that calling three fundamentally different things information is unscientific and leads to misunderstanding, which can cause serious problems. According to Professor Wu, the existence of the world is composed of matter and information, rather than matter and consciousness as the traditional world picture. Professor Wu is wrong with his description of the concept of real, and then he used this wrong understanding and unscientific concept of information to reclassify existence, which leads to his wrong direction in the study of ontology.